CLINICAL AND FUNCTIONAL CHARACTERISTICS OF PATIENTS AFTER Q-WAVE MYOCARDIAL INFARCTION DEPENDING ON THE METABOLIC SYNDROME PRESENCE OR ABSENCE - R. D. Kurbanov; N. U. Zakirov; N. B. Sayfiddinova; G. U. Mullabaeva; G. A. Nagaeva; Yu. G. Kevorkova (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To study the clinical and functional parameters of patients after acute Q-wave myocardial infarction (Q-MI) depending on the concomitant metabolic syndrome (MS). Material and methods. Men after Q-MI (n=79; aged 51.7±8.9 years) were included into the study. Patients were divided into two groups depending on the MS presence or absence. Doppler echocardiography and determination of the serum C-reactive protein (CRP) level were performed in all patients on the 10-14 days after Q-MI, and treadmill test was performed in 25 patients. Results. Left ventricular ejection fraction was 12% lower and the CRP level was 2 times higher in MS patients versus these in non-MS patients (p<0.01). The silent segment ST depression ≥1.0 mm were more often observed in MS patients compared with this in non-MS patients (40% vs 5%; respectively, p<0.05). Conclusion. The MS presence complicates the post-infarction period by early heart failure progression, characterized by elevated CRP levels and more frequent occurrence of silent myocardial ischemia.